The affecting of circular economy information disclosure on the corporate financial performance of companies listed on the Stock Exchange of Thailand - Poowadin , Promporn; Jangkloy, Usana; Leelamanothum, Amphaphron; Phrompoo, Putita; Chaepthaisong, Nualprang (KKBS Journal of Business Administration and Accountancy, 2025)
This research aims to study the relationship between circular economy disclosure and financial performance, and study the relationship between recycling disclosure, reducing disclosure, and reusing disclosure on financial performance. The sample group used in the research was 373 companies per year, which were sustainable stock companies in the Stock Exchange of Thailand during 2020-2022. The results of the study found that the circular economy disclosure on financial performance led to the understanding that the added value from circular economy disclosure of sustainable stock companies listed in the Stock Exchange of Thailand came from the overall circular economy disclosure, which consisted of recycling information, reducing information, improving information, and reusing information. And from the study of the disclosure of information on the circular economy by separating each component to see how it affects the disclosure of information on the circular economy and the financial performance, it was found that the disclosure of information on the circular economy by separating the 3 sub-components did not significantly affect the financial performance.